2010
DOI: 10.1007/s10578-010-0210-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parents’ and Children’s Automatic Thoughts in a College Student Sample

Abstract: Research demonstrates the importance of early social interactions in the development of schemas and automatic thoughts. It does not appear, however, that the existing research examines intergenerational correlations in automatic thoughts. As a result, this study explores the relationship between the automatic thoughts of parents and those of their college-age children in a sample of 252 college students and their mothers and fathers. Results of this study suggest that there are significant relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
7
1
1
Order By: Relevance
“…Moreover, maternal cognition was significantly correlated with children's negative cognition (Donnelly et al . 2011; Stark et al . 1996) and depressive symptoms (Tompson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, maternal cognition was significantly correlated with children's negative cognition (Donnelly et al . 2011; Stark et al . 1996) and depressive symptoms (Tompson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mothers' positive thoughts and self‐esteem can predict the same in their children (Donnelly et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In literature regarding depression, the studies on gender differences put forward different results. Some studies found that depression levels of males were higher than the females (For example, see [65]); some found that depression levels of females were higher than the males (For example, see [66]) and some found that gender did not create a difference on the depression level (for example, see [67][68][69]). In literature examining the relationship between stressful life events and depression, it is stated that life events are both stressful and an important risk factor when they accumulate [46,70].…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte Dilmaç, Aydoğan, Koruklu ve Deniz (2009) yaptıkları çalışmada ergenlerin mantık dışı inançları ve mükemmeliyetçilik düzeyleri ile aile beklentileri ve ebeveyn eleştiri boyutları arasında pozitif yönlü ilişki olduğunu, Aydın (2018) ise ergenlerin başarı ve rahatlık ile ilgili bilişsel hatalarının anne baba davranışları ile ilişkili olduğunu belirlemiştir. Bununla birlikte anne babaların olumlu otomatik düşünceleri ile çocuklarının olumlu otomatik düşünceleri arasında anlamı ilişki olduğu (Donnelly et al, 2011) ve annelerin mükemmeliyetçi ve otoriter tutumları ile kız çocuklarının mükemmeliyetçilik düzeyleri ve psikopatolojik semptomları arasında ilişki olduğunu gösteren çalışmalar da mevcuttur (Frost, Lahart ve Rosenblate, 1991). Bilişsel davranışçı terapi temelli psiko eğitim programları ile anne babalara kazandırılan bazı becerilerin çocuklardaki davranış ve uyum sorunlarını azaltmada etkili olduğu (David, 2014; Karbasi Amel, Karbasi Amel ve Erfan, 2018) ve anne babaların rasyonel olmayan inanç ve streslerine yapılan müdahalelerin dolaylı olarak çocuklarının rasyonel olmayan düşüncelerini etkilediğini (Özcan ve Arslan, 2018) ortaya koyan çalışmalar da bulunmaktadır.…”
Section: The Relationship Between Cognitive Distortions Related To Academic Achievement and Perceivedunclassified